Pragmatic Nonviolence: Working toward a Better World - Fitz-Gibbon, Andrew (Value Inquiry Book Series, 2021)
Written in dialogue format, Andrew Fitz-Gibbon's Pragmatic Nonviolence argues that nonviolence is the best hope for a better world. Human violence in all its forms-physical, psychological and systemic-cultural-is perhaps the greatest obstacle to well-being in personal and community life. Nonviolence as "a practice that, whenever possible, seeks the well-being of the Other, by refusing to use violence to solve problems, and by acting according to loving kindness" is the best antidote to human violence. By drawing on the philosophy of nonviolence, the American pragmatist tradition and recent empirical research, Pragmatic Nonviolence demonstrates that, rather than being merely theoretical, nonviolence is a truly practical approach toward personal and community well-being.